The WTO and the Doha Round : Walking on Two Legs - Hoekman, Bernard (World Bank, Washington, DC, 2012)
The Doha Round of the World Trade Organization (WTO) negotiations has been ongoing for 10 years, and given political cycles in major countries, there is not much hope for a rapid conclusion. The topics on the table are important, and in principle there is enough substance for all countries to gain from an agreement, but, unfortunately, too much emphasis has been placed on gains through market access alone. The Doha Round is about much more than market access. Concluding the talks arguably requires greater recognition of the value of trade policy disciplines that will be part of any agreement. The WTO is not just a market access negotiating forum; it is also a multilateral umbrella through which governments can agree on rules of the game for other trade-related policies. Given the slow progress of the Round, greater emphasis could be put on leveraging existing WTO bodies to enhance the transparency of nontariff measures, address regulatory concerns that impede liberalization of trade in services, and launch a dialogue on domestic economic policies that can create negative spillover effects for trading partners.